Pengaruh Konseling Kelompok dengan Terapi Syukur Terhadap Peningkatan Self Compassion Santri SMP di Pondok Pesantren Al-Manar Gampong Lampermei, Kecamatan Krueng Barona Jaya, Kabupaten Aceh Besar - Jarnawi, Jarnawi; Duri, Rofiqa; Indra, Syaiful; P, Hermida Pitri (Jurnal Bimbingan dan Konseling Islam, 2024)
It is very important for teenagers today to have self-compassion for themselves in everyday life, because by having high self-compassion, students are able to love and give affection to themselves, tend to have views and push for more positive things, and are able to accept things. failures experienced by humans in general. However, some students still have low self-compassion, so they tend to judge themselves and tend to feel separated from their surroundings. The aim of this research is to determine the description of self-compassion in santri, as well as to determine the effect of group counseling with gratitude therapy on increasing self-compassion in santri. This research is a type of quantitative research using a quantitative experimental approach. The population in this study was students at junior high school level, class VIII, totaling 225 students. Samples were taken using purposive sampling techniques among students. The data collection technique used was the self-compassion scale, then the data was analyzed using descriptive analysis and the Wilcoxon test. The results of this research show that the self-compassion of students is in the medium category. Meanwhile, a Wilcoxon signed ranks test analysis was carried out, a significant value (2-tailed) of 0.003 <0.05 was obtained, which means that Ho was rejected and Ha was accepted, which shows that there is an influence of group counseling with gratitude therapy on increasing the self-compassion of students at the Al-Islam Islamic Boarding School. Manar.